Positive electrode material and preparation method thereof, positive electrode, secondary battery and electric equipment
By introducing core material (LiaAd)1+x(M1-bEb)1-x(O1-cL2c)2 and a shell with high WO2.72 mass content into the lithium-rich transition metal layered oxide, the structural fracture and battery capacity attenuation problems caused by oxygen atom oxidation are solved, and the positive electrode material with high stability and excellent rate performance is achieved, which improves the overall performance of the secondary battery.
Patent Information
- Application Number
- CN202311767571.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2025-04-15
AI Technical Summary
Lithium-rich transition metal layered oxides are prone to oxygen atom oxidation during battery cycles, resulting in material structure rupture, phase transformation and rapid attenuation of battery capacity, limiting its large-scale application.
The core material (LiaAd) 1+x(M1-bEb) 1-x(O1-cL2c) 2 and the shell material WO2.72 are used to form a shell with high WO2.72 mass content through the second calcination, which inhibits the detachment of oxygen atoms and improves structural stability.
It significantly improves the structural stability and rate performance of the positive electrode material, extends the cycle life of the battery, and improves the capacity and charging and discharging efficiency of the secondary battery.
Smart Images

Figure BDA0004620571160000111 
Figure BDA0004620571160000121 
Figure BDA0004620571160000131
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of batteries, and particularly to a cathode material, a preparation method thereof, a cathode, a secondary battery, and an electrical device. Background Art
[0002] The lithium-rich transition metal layered oxide with both high charge-discharge capacity and low cost is one of the next-generation cathode materials with great application prospects. However, during the battery cycling process, it is extremely prone to irreversible oxidation of oxygen atoms. The oxygen atoms in the material will generate oxygen and escape, which will not only reduce the first-cycle efficiency of the battery, but also cause structural rupture and phase transformation of the material, further resulting in gradual inactivation of the material and rapid attenuation of the battery capacity, seriously restricting the large-scale application of the lithium-rich transition metal layered oxide. Summary of the Invention
[0003] In view of this, the embodiments of the present application provide a cathode material, which has a high charge-discharge energy, excellent electronic conductivity and ionic conductivity, and can exhibit good structural stability during the charge-discharge cycle of the battery, and can be used to provide a secondary battery with a higher capacity, better cycle stability and better rate performance.
[0004] The first aspect of the embodiments of the present application provides a cathode material, including a core and a shell layer coated on the core; wherein, the material of the core includes (Li a A d ) 1+x (M 1-b E b ) 1-x (O 1-c L 2c )2, where 0 < x ≤ 0.33, 0 < a ≤ 1, 0 ≤ b < 1, 0 ≤ c < 1, 0 ≤ d < 1; M includes at least one of Ni, Co, and Mn; A includes at least one of Na, K, and Mg; E includes at least one of Cr, Al, Mg, Co, Ce, Zr, Mo, Nb, W, Ta, B, Y, Sr, V, and Ti; L includes at least one of F, Cl, and Br;
[0005] The material of the shell layer includes WO 2.72 , and the mass percentage of WO 2.72 in the shell layer ≥ 90%.
[0006] Based on the inherent properties of the core material, the cathode material has a high charge-discharge capacity; at the same time, the shell layer material with a high WO 2.72 mass content has more oxygen vacancies and a stable structure, which can effectively inhibit (Li a A d ) 1+x (M 1-bE b ) 1-x (O 1-c L 2c )2, improves the structural stability of the positive electrode material and optimizes its interface, thereby improving the cycle performance of the battery. 2.72 It has good electronic conductivity and ionic conductivity, and can effectively improve the rate performance of the positive electrode material. Therefore, the above positive electrode material can be used to provide a secondary battery with high capacity, good cycle performance and excellent rate performance.
[0007] A second aspect of the present application provides a method for preparing a positive electrode material, comprising:
[0008] According to the (Li a A d ) 1+x (M 1-b E b ) 1-x (O 1-c L 2c )2, and performing a first calcination in an air atmosphere to obtain a first material; wherein M includes at least one of Ni, Co and Mn; A includes at least one of Na, K and Mg; E includes at least one of Al, Mg, Cr, Co, Ce, Zr, Mo, Nb, W, Ta, B, Y, Sr, V and Ti; and L includes at least one of F, Cl and Br;
[0009] The first material, tungsten source, oxalic acid and solvent are mixed to obtain a mixture; the mixture is heated to react, and the obtained solidified material is subjected to a second calcination under a protective atmosphere to obtain a positive electrode material; the positive electrode material comprises a core and a shell layer coated on the core; wherein the core comprises (Li a A d ) 1+x (M 1-b E b ) 1-x (O 1-c L 2c )2, where 0 <x≤0.33,0<a≤1,0≤b<1,0≤c<1,0≤d<1;
[0010] The material of the shell layer includes WO 2.72 , and the WO 2.72 The mass percentage in the shell layer is ≥ 90%.
[0011] The preparation method is simple and easy to implement, has strong process reliability, high production efficiency, and can realize large-scale industrial production.
[0012] In the third aspect of the embodiments of the present application, a positive electrode is provided, including the positive electrode material provided in the first aspect of the embodiments of the present application. Due to the positive electrode material provided in the embodiments of the present application, this positive electrode can be used to provide a secondary battery with both high capacity, excellent cycle performance, and good rate performance.
[0013] In the fourth aspect of the embodiments of the present application, a secondary battery is provided, including the positive electrode provided in the second aspect of the embodiments of the present application. This secondary battery can have both high capacity, excellent cycle performance, and good rate performance.
[0014] In the fifth aspect of the embodiments of the present application, an electrical device is provided, including the secondary battery provided in the embodiments of the present application. Due to being powered by the secondary battery provided in the embodiments of the present application, this electrical device can have good endurance, high charging efficiency, and good market prospects. Detailed implementation manners
[0015] The lithium-rich transition metal layered oxide (Li 1+x M 1-x O2, 0 < x ≤ 0.33) not only has a high capacity, but also can have a certain lithium compensation effect by increasing the proportion of the lithium-rich phase in the material. Therefore, the lithium-rich transition metal layered oxide is a very promising positive electrode material. However, during the high-voltage formation process of the battery, it is extremely easy to oxidize and release oxygen at high voltage, and during the cycling process, the oxygen atoms on the surface of the material are also relatively easy to escape. This process will be accompanied by phase transformation (from the layered structure to the spinel phase and the rock salt phase) and the rupture of the material structure, and even induce cation mixing, affecting the performance of the battery. In addition, Li 1+x M 1-x O2 has poor conductivity, and a relatively thick interfacial film is easily formed on its surface under high-voltage formation conditions, reducing the rate performance of the battery. Therefore, the large-scale application of the lithium-rich transition metal layered oxide, whether as a positive electrode material or a lithium compensation material, will be limited to a certain extent. Although it is common knowledge in the industry to solve the above problems through ion doping or material nanosizing, the improvement effect is limited.
[0016] To solve the above technical problems, the embodiments of the present application provide a positive electrode material, including a core and a shell layer coated on the core; wherein, the material of the core includes (Li a A d ) 1+x (M 1-b E b ) 1-x (O 1-c L 2c)2, where 0 < x ≤ 0.33, 0 < a ≤ 1, 0 ≤ b < 1, 0 ≤ c < 1, 0 ≤ d < 1; M includes at least one of Ni, Co, and Mn; A includes at least one of Na, K, and Mg; E includes at least one of Cr, Al, Mg, Co, Ce, Zr, Mo, Nb, W, Ta, B, Y, Sr, V, and Ti; L includes at least one of F, Cl, and Br; it is understood that when b, c, and d are all 0 at the same time, the material of the above core is Li 1+x M 1-x O2;
[0017] The material of the shell layer includes WO 2.72 , and the mass percentage of the WO 2.72 in the shell layer ≥ 90%.
[0018] Based on the inherent properties of the core material, the cathode material has a high charge-discharge capacity. Further, doping Li 1+ x M 1-x O2 can further improve the structural stability and / or conductivity of Li 1+x M 1-x O2, thereby further improving the cycle performance and / or rate performance of the final secondary battery. More importantly, WO 2.72 with oxygen vacancies in the molecular structure has good structural stability and electrochemical stability. Therefore, the shell material with a high WO 2.72 mass content has more oxygen vacancies and a stable structure, which can effectively inhibit the escape of oxygen atoms from (Li a A d ) 1+x (M 1-b E b ) 1-x (O 1-c L 2c )2, and the physical barrier effect of the shell layer can also reduce the risk of oxygen atoms escaping due to side reactions occurring when the core contacts the electrolyte (for example, the electrolyte solution), thereby significantly improving the structural stability of the cathode material and optimizing its interface, and further improving the cycle performance of the battery. In addition, WO 2.72 has both good electronic conductivity and ionic conductivity, which can effectively improve the rate performance of the cathode material. Therefore, the above cathode material can be used to provide a secondary battery with a higher capacity, better cycle performance, and better rate performance.
[0019] In the embodiments of the present application, the mass ratio of WO 2.72 in the shell layer can be but is not limited to 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.5%, 100%, etc. If WO 2.72If the mass ratio of WO is too low, the content of oxygen vacancies in the shell material will decrease, which will not only affect the stability of the shell material itself, but also weaken the inhibitory effect on the escape of oxygen atoms in the core, resulting in poor cycle performance of the final battery. If other components in the shell are low-conductivity materials, the rate performance of the final battery will also be reduced. In the embodiment of this application, the characterization of WO 2.72 The methods include X-ray diffraction test, transmission electron microscopy (TEM), energy dispersive spectrometer (EDS), and X-ray photoelectron spectroscopy (XPS).
[0020] In the embodiment of the present application, when WO 2.72 When the mass proportion of WO is less than 100%, the remaining components may be, but are not limited to, impurities adhering to the surface of the positive electrode material during the preparation process, and / or impurities intentionally doped on WO 2.72 The doping elements in .
[0021] In some embodiments of the present application, the shell layer further includes a doping element, and the doping element includes at least one of Ni, Co or Mn. In some specific embodiments, the above doping element is doped in WO 2.72 The ions formed by the above three elements have a lower valence than tungsten ions. 2.72 The lattice of WO can be improved 2.72 The ratio of oxygen vacancies in the core (Li a A d ) 1+x (M 1-b E b ) 1-x (O 1-c L 2c )2 During the charge and discharge process, oxygen atoms are released, which can further improve the structural stability of the positive electrode material during the charge and discharge process, and then further improve the cycle performance of the final battery. It can be understood that the above doping elements are doped into WO 2.72 lattice, which may cause changes in lattice parameters and cause WO 2.72 The molar quantity of O element in WO changes slightly, but due to the 2.72 Even if the molar amount of O element is slightly changed in this specific lattice, it should be considered as the protection scope of this application.
[0022] In some embodiments of the present application, the mass percentage of the doping element in the shell layer is 0.05%-10%. Controlling the mass percentage of the doping element within the above range can be done without affecting the WO 2.72 Under the condition of its own structural stability, it effectively improves WO 2.72 The proportion of oxygen vacancies in the shell can reduce the interface impedance; at the same time, it is also easier to prepare. Exemplarily, the mass percentage of the doping element in the shell layer can be 0.05%, 0.1%, 0.15%, 0.20%, 0.25%, 0.30%, 0.50%, 0.80%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 3.0%, 3.5%, 4.0%, 5.0%, 5.5%, 6.0%, 7.0%, 8.0%, 9.0%, 9.5%, etc. In some specific embodiments, the mass percentage of the doping element in the shell layer is 0.1%-3%. In this way, the WO in the shell layer can be effectively increased. 2.72 The ratio of oxygen vacancies can also ensure that WO 2.72 The structural stability is good, which is more conducive to the cycle performance of the battery. In the embodiment of the present application, XPS can be used to test the mass proportion of the doping element in the shell layer.
[0023] In some embodiments of the present application, the thickness of the shell is in the range of 5nm-200nm. In some specific embodiments, the thickness of the shell is in the range of 5nm-100nm. In this way, on the one hand, there is a good effect of fixing oxygen and improving the conductivity of the material, and on the other hand, it can effectively avoid the side reaction caused by direct contact between the positive electrode material and the electrolyte, thereby protecting the positive electrode material; illustratively, the thickness of the shell can be but is not limited to 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 110nm, 120nm, 130nm, 150nm, 180nm, 200nm, etc.
[0024] In some embodiments of the present application, based on the mass of the positive electrode material, the mass proportion of the tungsten element in the shell layer in the positive electrode material is in the range of 0.05%-5%. 2.72The mass proportion of tungsten in the shell layer is at least 90%, which controls the mass proportion of tungsten in the shell layer in the positive electrode material within the above range, and can also represent that the proportion of the shell material in the positive electrode material is within a suitable range; in particular, when the thickness of the shell layer is constant, the mass proportion of tungsten in the shell layer in the positive electrode material is further regulated, and the density or compactness of the shell material can be controlled within a suitable range. In some specific embodiments, the mass proportion of tungsten in the shell layer in the positive electrode material is in the range of 0.2%-1%. Considering that there may be doped elements in the shell layer, the mass proportion of tungsten in the shell layer is controlled within the above range, and the remaining mass proportion, except for WO 2.72 The O element in the shell layer has a mass proportion of doping elements that is not too much. In this way, the proportion of doping elements in the shell layer is controlled within a more appropriate range, which is more conducive to improving the structural stability, ion conductivity and electronic conductivity of the positive electrode material. In some specific embodiments, the mass proportion of tungsten elements in the shell layer in the positive electrode material is in the range of 0.3%-0.6%. Exemplarily, the mass proportion of tungsten elements in the shell layer in the positive electrode material can be, but is not limited to, 0.05%, 0.10%, 0.15%, 0.20%, 0.30%, 0.50%, 0.80%, 1.00%, 1.50%, 2.00%, 2.50%, 3.00%, 3.50%, 4.00%, 4.50%, 5.00%, etc. In the embodiments of the present application, an X-ray fluorescence spectrometer (XRF), an energy dispersive spectrometer (EDS), or an X-ray photoelectron spectroscopy (XPS) can be used to test the mass proportion of tungsten in the positive electrode material.
[0025] Understandably, due to the WO 2.72 It has good electronic conductivity, which is reflected in the electrochemical performance as improving the rate performance of the positive electrode material, and can be manifested in the intrinsic parameters of the positive electrode material as reducing the powder resistivity of the positive electrode material. In some embodiments of the present application, a powder resistivity tester is used to measure the powder resistivity of the positive electrode material. Under a test pressure of 12KN, the powder resistivity of the positive electrode material is in the range of 0.005Ω·cm-200Ω·cm. Exemplarily, under the above test conditions, the powder resistivity of the positive electrode material can be, but is not limited to, 0.005Ω·cm, 0.01Ω·cm, 0.05Ω·cm, 0.10Ω·cm, 0.5Ω·cm, 1.0Ω·cm, 2.5Ω·cm, 5.0Ω·cm, 10.0Ω·cm, 15.0Ω·cm, 20.0Ω·cm, 50.0Ω·cm, 100Ω·cm, 200Ω·cm, etc.
[0026] In some implementations of the present application, the kernel includes (Li a A d ) 1+x (M 1-b E b ) 1-x (O 1-c L 2c )2 single crystal particles. In some specific embodiments, the core is (Li a A d ) 1+x (M 1-b E b ) 1-x (O 1-c L 2c )2 Single crystal particles. Single crystal particles can overcome the problem of polycrystalline materials being prone to cracks at the grain boundaries, and avoid the situation where the uncoated interface is in contact with the electrolyte (e.g., electrolyte) in the battery due to grain boundary rupture, which aggravates the deoxidation of the material, thereby making the positive electrode material continuously stable during the charge and discharge cycle, thereby improving the long-cycle performance of the final battery.
[0027] In some embodiments of the present application, the D50 particle size of the positive electrode material is in the range of 3μm-5.5μm. By controlling the particle size of the positive electrode material within the above range, firstly, the transmission path of the active ions in the positive electrode material can be regulated to be shorter, which is conducive to ensuring the rate performance of the final battery; secondly, it is conducive to achieving a higher compaction density, thereby increasing the capacity of the final battery. Exemplarily, the D50 of the positive electrode material can be, but is not limited to, 3.0μm, 3.5μm, 4.0μm, 4.5μm, 5.0μm, 5.5μm, etc. In the embodiment of the present application, a laser particle size analyzer can be used to test the D50 particle size of the positive electrode material.
[0028] The present application also provides a method for preparing a positive electrode material, which can be used to prepare the positive electrode material, comprising the following steps:
[0029] S01, according to the (Li a A d ) 1+x (M 1-b E b ) 1-x (O 1-c L 2c )2, and performing a first calcination in an air atmosphere to obtain a first material; wherein M includes at least one of Ni, Co and Mn; A includes at least one of Na, K and Mg; E includes at least one of Al, Mg, Cr, Co, Ce, Zr, Mo, Nb, W, Ta, B, Y, Sr, V and Ti; and L includes at least one of F, Cl and Br;
[0030] S02, mixing the first material, tungsten source, oxalic acid and solvent to obtain a mixture; heating the mixture to react, and performing a second calcination on the obtained solidified material under a protective atmosphere to obtain a positive electrode material; the positive electrode material comprises a core and a shell layer coated on the core; wherein the core comprises (Li a A d ) 1+x (M 1-b E b ) 1-x (O 1-c L 2c )2, where 0 <x≤0.33,0<a≤1,0≤b<1,0≤c<1,0≤d<1;
[0031] The material of the shell layer includes WO 2.72 , and WO 2.72 The mass percentage in the shell layer is ≥ 90%.
[0032] The preparation method is simple and easy to implement, has high production efficiency, and can realize large-scale industrial production.
[0033] In the embodiment of the present application, in step S01, according to common knowledge in the field, some raw materials can be relatively excessive, for example, the lithium source and the A source can be relatively excessive. In some embodiments of the present application, the ratio of the sum of the molar amounts of the lithium element and the A element to the molar amount of the M element is (1.4-1.65):1.
[0034] In the embodiment of the present application, in step S01, the lithium source, A source, M source, E source and L source can be selected from any compound known in the art that is suitable for the preparation of lithium-rich transition metal oxides. For example, a salt or hydroxide of lithium element or A element. Exemplarily, the lithium source includes but is not limited to at least one of lithium carbonate, lithium acetate, lithium hydroxide, etc.; when the A element is potassium element, the above-mentioned A source includes but is not limited to at least one of potassium carbonate, potassium acetate, potassium hydroxide, etc. The above-mentioned M source includes but is not limited to manganese hydroxide or salt (for example, manganese carbonate), cobalt hydroxide or salt (for example, cobalt carbonate), nickel hydroxide or salt (for example, nickel carbonate), (Mn 2 / 3 Co 1 / 6 Ni 1 / 6 )(OH)2、(Mn 2 / 3 Co 1 / 6 Ni 1 / 6 )CO3, and those skilled in the art can select as needed. The selection of other element sources will not be described in detail in this application.
[0035] In some embodiments of the present application, the M source is a granular material, and its D50 is 3 μm-5 μm, so that it is easier to obtain a cathode material with a target D50 particle size. For example, the D50 of the M source can be, but is not limited to, 3.0 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4.0 μm, 4.2 μm, 4.5 μm, 4.8 μm, 5.0 μm, etc.
[0036] In some embodiments of the present application, in step S01, the first calcination condition is to keep the temperature at 950°C-1050°C for 8h-15h. In this way, the core material can be promoted to have a single crystal structure. Exemplarily, the holding temperature of the first calcination can be, but not limited to, 950°C, 975°C, 1000°C, 1025°C, 1050°C, etc. Exemplarily, the holding time of the first calcination can be, but not limited to, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, etc.
[0037] In some embodiments of the present application, step S01 further includes crushing and screening the product obtained by the first calcination to obtain the first material.
[0038] In some embodiments of the present application, in step S02, the molar ratio of the tungsten element in the tungsten source to the oxalic acid is 1:(6-10). 2.72 , which is also beneficial to further improve the WO 2.72 For example, the ratio of the amount of tungsten element in the tungsten source to the amount of oxalic acid may be, but is not limited to, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5, 1:10, etc. In some embodiments of the present application, in step S02, the tungsten source includes, but is not limited to, WCl6, Na2WO4, K2WO4, (NH4)2WO4.
[0039] In some embodiments of the present application, step S02 further includes adding a compound containing a doping element to the mixture, wherein the doping element includes but is not limited to at least one of Ni, Co and Mn. The compound containing the doping element is added to the mixture, and during the second calcination process, the doping element can be doped into the shell material to obtain a shell with the doping element. The above-mentioned compound containing the doping element includes but is not limited to at least one of manganese oxide, hydroxide or salt (e.g., manganese carbonate), cobalt tungsten oxide, hydroxide or salt (e.g., cobalt carbonate), nickel tungsten oxide, hydroxide or salt (e.g., nickel carbonate).
[0040] In some embodiments of the present application, in step S02, the first material, the tungsten source, and oxalic acid are added to a solvent and stirred for 10 min-30 min to obtain a mixture.
[0041] In some embodiments of the present application, the above-mentioned solvent includes but is not limited to at least one of isopropanol and ethylene glycol.
[0042] In some embodiments of the present application, in step S02, the conditions for the heating treatment are: keeping the mixture at 130°C-180°C for 18h-36h, that is, performing hydrothermal insulation at 130°C-180°C for 18h-36h.
[0043] In step S02, considering that the mixture after the heating reaction may still contain solvent, in some embodiments, the mixture after the heating reaction is sequentially subjected to solid-liquid separation and drying, and then the obtained solidified material is subjected to a second calcination under a protective atmosphere. In some specific embodiments, the above-mentioned solid-liquid separation is filtration.
[0044] In some embodiments of the present application, in step S02, the conditions for the second calcination are: keep warm at 300°C-700°C for 3h-8h under a protective atmosphere. In this way, a stable shell can be formed on the surface of the first material to obtain a positive electrode material without destroying the structure of the core material. In this process, the M element on the surface of the first material can also be partially doped into the shell. It can be understood that when the mixture includes a compound containing a doping element, the doping element will be doped into the shell during the second calcination. Exemplarily, the temperature of the second calcination can be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, etc. Exemplarily, the duration of the second calcination can be 3h, 4h, 5h, 6h, 7h, 8h, etc.
[0045] In the embodiments of the present application, the protective atmosphere includes but is not limited to nitrogen atmosphere, argon atmosphere, a mixed atmosphere of nitrogen and argon, etc.
[0046] The present application also provides a positive electrode, including the positive electrode material provided in the present application. Due to the positive electrode material provided in the present application, the positive electrode can be used to provide a secondary battery with higher capacity, better cycle performance and better rate performance.
[0047] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode material layer includes a positive electrode active material, a binder, and an optional conductive agent.
[0048] In the embodiment of the present application, all the positive electrode active materials in the positive electrode material layer may be the aforementioned positive electrode materials provided in the embodiment of the present application; or the positive electrode active materials may include the positive electrode materials provided in the embodiment of the present application and other positive electrode active materials. Among them, other positive electrode active materials may be selected from any known positive electrode active materials of lithium-ion batteries, for example, at least one of phosphate-based positive electrode active materials, oxide positive electrode active materials, and polyanion-type positive electrode active materials. Among them, the phosphate-based positive electrode active materials include but are not limited to modified or unmodified lithium iron phosphate. The oxide positive electrode active materials include but are not limited to one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, and lithium manganese oxide. Polyanion-type positive electrode active materials include but are not limited to modified or unmodified lithium vanadium phosphate, etc.
[0049] In the embodiment of the present application, the material of the positive electrode current collector can be any material known in the art. The binder and the conductive agent can also be selected from any conductive agent and binder known in the art that are suitable for positive electrodes.
[0050] The embodiment of the present application also provides a secondary battery, including the positive electrode provided in the embodiment of the present application. The secondary battery can have a higher capacity, better cycle performance and better rate performance.
[0051] In some embodiments of the present application, the secondary battery comprises the positive electrode, the negative electrode and an electrolyte between the positive electrode and the negative electrode. In the embodiments of the present application, the negative electrode can be any negative electrode known in the art.
[0052] In the embodiment of the present application, the secondary battery may be a solid-state battery using a solid electrolyte, a liquid battery using a liquid electrolyte, or a semi-solid-state battery.
[0053] In some embodiments of the present application, the secondary battery includes a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode.
[0054] The present application also provides an electric device, including but not limited to the aforementioned secondary battery provided in the present application. Since the secondary battery provided in the present application is used to power it, the electric device can have a good endurance, high charging efficiency, and good market prospects.
[0055] In some implementations of the present application, the above-mentioned electrical equipment includes but is not limited to vehicles and consumer electronic products. Among them, vehicles include but are not limited to new energy vehicles, power-assisted electric vehicles, etc.
[0056] The technical solution of the present application is further illustrated by multiple embodiments below.
[0057] Example 1
[0058] (1) A lithium source (specifically Li2CO3) and an M source (specifically Mn 0.54 Co 0.13 Ni 0.13 (OH) 1.6 ), E source (specifically ZrO2 nanopowder, V2O5 nanopowder) are evenly mixed according to the proportion of the core material to be prepared, wherein the molar ratio of Li:(Mn+Co+Ni+Zr+V) is 1.58:1; and in an air atmosphere, it is kept warm at 995°C for 12 hours, and then crushed and sieved in turn to obtain the first material.
[0059] (2) The first material is added to an isopropanol solution and stirred, and a tungsten source (specifically WCl6), a compound containing an doping element (specifically Ni(NO3)2) and oxalic acid are added, wherein the molar ratio of WCl6 to oxalic acid is 1:10. After stirring for 30 minutes, the solution is transferred to a reactor, hydrothermally kept at 160°C for 24 hours, filtered, vacuum dried, and calcined at 350°C for 5 hours in a nitrogen atmosphere to obtain a positive electrode material.
[0060] Example 2-Example 5
[0061] The difference between Example 2 to Example 5 and Example 1 is that in step (2), the amount of WCl6 added is fine-tuned, and the parameters of the obtained positive electrode materials are summarized in Table 1.
[0062] Example 6
[0063] (1) A lithium source (specifically Li2CO3) and an M source (specifically Mn 0.54 Co 0.13 Ni 0.13 (OH) 1.6 ), E source (specifically ZrO2 nanopowder, WO3 nanopowder) are evenly mixed according to the proportion of the core material to be prepared, wherein the molar ratio of Li:(Mn+Co+Ni+Zr+W) is 1.59:1; and in an air atmosphere, it is kept warm at 990°C for 13h, and then crushed and sieved in turn to obtain the first material.
[0064] (2) The first material is added to an isopropanol solution and stirred, and a tungsten source (specifically WCl6), a compound containing an doping element (specifically Ni(NO3)2) and oxalic acid are added, wherein the molar ratio of WCl6 to oxalic acid is 1:10. After stirring for 30 minutes, the solution is transferred to a reactor, hydrothermally kept at 160°C for 24 hours, filtered, vacuum dried, and calcined at 450°C for 3 hours in a nitrogen atmosphere to obtain a positive electrode material.
[0065] Example 7
[0066] (1) A lithium source (specifically Li2CO3) and an M source (specifically Mn 0.54 Co 0.13 Ni 0.13 (OH) 1.6 ), E source (specifically ZrO2 nanopowder, Al2O3 nanopowder) are evenly mixed according to the proportion of the core material to be prepared, wherein the molar ratio of Li:(Mn+Co+Ni+Zr+Al) is 1.58:1; and in an air atmosphere, it is kept warm at 1000°C for 12 hours, and then crushed and sieved in turn to obtain the first material.
[0067] (2) The first material is added to an isopropanol solution and stirred, and a tungsten source (specifically WCl6), a compound containing an doping element (specifically Ni(NO3)2) and oxalic acid are added, wherein the molar ratio of WCl6 to oxalic acid is 1:10. After stirring for 30 minutes, the solution is transferred to a reactor, hydrothermally kept at 160°C for 24 hours, filtered, vacuum dried, and calcined at 550°C for 3 hours in a nitrogen atmosphere to obtain a positive electrode material.
[0068] Example 8 and Example 9
[0069] The difference from Example 1 is that in step (2), the amount of WCl6 added is fine-tuned.
[0070] Example 10
[0071] The difference from Example 1 is that in step (1), the M source is a large particle precursor with D50=10.5 μm, and in step (2), the amount of WCl6 added is fine-tuned.
[0072] Embodiment 11
[0073] The difference from Example 1 is that in step (1), the molar ratio of Li:(Mn+Co+Ni+Zr+V) is 1.56:1, and in step (2), the amount of WCl6 added is fine-tuned.
[0074] Example 12-Example 15
[0075] The difference from Example 1 is that in step (2), the amount of Ni(NO3)2 added is fine-tuned.
[0076] Example 16
[0077] (1) A lithium source (specifically Li2CO3) and an M source (specifically Mn 0.54 Co 0.13 Ni 0.13 (OH) 1.6) bodies are uniformly mixed according to the proportion of the core material to be prepared, wherein the molar ratio of Li:(Mn+Co+Ni) is 1.58:1; and are kept warm at 995°C for 12 hours in an air atmosphere, and are crushed and sieved in sequence to obtain a first material.
[0078] (2) The first material is added to an isopropanol solution and stirred, and a tungsten source (specifically WCl6), a compound containing an doping element (specifically Ni(NO3)2) and oxalic acid are added, wherein the molar ratio of WCl6 to oxalic acid is 1:10. After stirring for 30 minutes, the solution is transferred to a reactor, hydrothermally kept at 160°C for 24 hours, filtered, vacuum dried, and calcined at 350°C for 5 hours in a nitrogen atmosphere to obtain a positive electrode material.
[0079] Embodiment 17
[0080] (1) A lithium source (specifically Li2CO3) and an M source (specifically Mn 0.54 Co 0.13 Ni 0.13 (OH) 1.6 ), E source (specifically ZrO2 nanopowder, V2O5 nanopowder) are evenly mixed according to the proportion of the core material to be prepared, wherein the molar ratio of Li:(Mn+Co+Ni+Zr+V) is 1.58:1; and in an air atmosphere, it is kept warm at 995°C for 12 hours, and then crushed and sieved in turn to obtain the first material.
[0081] (2) The first material is added to an isopropanol solution and stirred, and a tungsten source (specifically WCl6) and oxalic acid are added, wherein the molar ratio of WCl6 to oxalic acid is 1:10. After stirring for 30 minutes, the solution is transferred to a reactor and hydrothermally kept at 160°C for 24 hours. The solution is filtered and vacuum dried, and calcined at 350°C for 5 hours in a nitrogen atmosphere to obtain a positive electrode material.
[0082] Embodiment 18
[0083] (1) A lithium source (specifically Li2CO3) and an M source (specifically Mn 0.54 Co 0.13 Ni 0.13 (OH) 1.6 ), E source (specifically ZrO2 nanopowder, V2O5 nanopowder) are evenly mixed according to the proportion of the core material to be prepared, wherein the molar ratio of Li:(Mn+Co+Ni+Zr+V) is 1.58:1; and in an air atmosphere, it is kept warm at 945°C for 12 hours, and then crushed and sieved in sequence to obtain the first material.
[0084] (2) The first material is added to an isopropanol solution and stirred, and a tungsten source (specifically WCl6), a compound containing an doping element (specifically Ni(NO3)2) and oxalic acid are added, wherein the molar ratio of WCl6 to oxalic acid is 1:10. After stirring for 30 minutes, the solution is transferred to a reactor, hydrothermally kept at 160°C for 24 hours, filtered, vacuum dried, and calcined at 350°C for 5 hours in a nitrogen atmosphere to obtain a positive electrode material.
[0085] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are provided.
[0086] Comparative Example 1
[0087] The lithium source (specifically Li2CO3), the M source with D50 = 3.8 μm (specifically Mn 0.54 Co 0.13 Ni 0.13 (OH) 1.6 ), E source (specifically ZrO2 nanopowder, V2O5 nanopowder) are mixed uniformly in the same proportion as in Example 1, wherein the molar ratio of Li:(Mn+Co+Ni+Zr+V) is 1.58:1; and in an air atmosphere, they are kept warm at 1000°C for 12 hours, and then crushed and sieved in turn to obtain the positive electrode material.
[0088] Comparative Example 2
[0089] The lithium source (specifically Li2CO3), the M source with D50 = 10.5 μm (specifically Mn 0.54 Co 0.13 Ni 0.13 (OH) 1.6 ), E source (specifically ZrO2 nanopowder, Al2O3 nanopowder) are mixed uniformly in the same proportion as in Example 7, wherein the molar ratio of Li:(Mn+Co+Ni+Zr+Al) is 1.58:1; and in an air atmosphere, they are kept warm at 940°C for 12 hours, and then crushed and sieved in turn to obtain the positive electrode material.
[0090] Comparative Example 3
[0091] (1) A lithium source (specifically Li2CO3) and an M source (specifically Mn 0.54 Co 0.13 Ni 0.13 (OH) 1.6 ), E source (specifically ZrO2 nanopowder, V2O5 nanopowder) are evenly mixed according to the proportion of the core material to be prepared, wherein the molar ratio of Li:(Mn+Co+Ni+Zr+V) is 1.6:1; and in an air atmosphere, it is kept warm at 995°C for 12 hours, and then crushed and sieved in turn to obtain the first material.
[0092] (2) The first material, β-WO 2.9 , WO 2.72 The nanopowders are mixed evenly, including β-WO 2.9 , WO 2.72 The mass ratio is 9:1, and then calcined at 450°C for 5h to obtain the finished positive electrode material.
[0093] Table 1
[0094]
[0095] Performance Testing
[0096] (1) The positive electrode material, binder (specifically PVDF) and conductive agent (specifically conductive carbon black) of each embodiment and comparative example were mixed in a mass ratio of 95:2:3, dispersed in a solvent (specifically N-methylpyrrolidone), and mixed evenly to obtain a positive electrode slurry; the solid content of each positive electrode slurry was the same.
[0097] The positive electrode slurry was coated on the opposite sides of the positive electrode current collector (specifically, aluminum foil), dried, rolled and cut to obtain the positive electrodes of various embodiments and comparative examples.
[0098] The positive electrodes, separators and lithium metal sheets are stacked, assembled in a glove box, and injected with electrolyte to prepare a button battery. The electrolyte is an organic solvent containing lithium salt, wherein the lithium salt concentration is 1 mol / L, and the mass ratio of the organic solvent is 3:6:1 of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate and 1% by mass of vinylene carbonate.
[0099] (2) First discharge gram capacity and first cycle efficiency test: Each test battery prepared in the above steps was connected to a battery cabinet, charged to 4.8V at a constant current of 0.1C, then charged at a constant voltage to a current ≤ 0.02C, left to stand for 30 minutes, and then discharged to 3V at a constant current of 0.1C. The first charged capacity was recorded to calculate the first charge gram capacity of the battery, and the first cycle efficiency = first discharge capacity / first charge capacity × 100%. The results are summarized in Table 2.
[0100] Cycle performance test: At 25±2℃, charge to 4.6V at 1C constant current, then charge at constant voltage to current ≤0.02C, let stand for 10min, and then discharge to 3.0V at 1C constant current. Record the battery capacity retention rate after 100 cycles, and the results are summarized in Table 2.
[0101] Rate performance test: The discharge capacity of each battery at 2C and 0.1C was tested at 25±2℃, with a voltage range of 2.5V-4.3V. The test results are summarized in Table 2.
[0102] AC impedance: At 25°C, the frequency range is: 100kHz~0.05Hz, the amplitude is 5mV, the AC impedance of each battery is tested, and then Rs and Rct are obtained by fitting through Zview software. Among them, the ohmic impedance (Rs) and charge transfer impedance (Rct) are summarized in Table 2.
[0103] Table 2
[0104]
[0105]
[0106] Combining the data in Table 1 and Table 2, it can be seen that the positive electrode material provided in the embodiment of the present application has both a high first discharge capacity and a good first cycle discharge efficiency. More importantly, compared with the positive electrode material in the comparative example, the room temperature cycle capacity retention rate of the positive electrode material in the embodiment is significantly improved, indicating that the positive electrode material in the embodiment of the present application exhibits high structural stability during the long cycle of the battery; at the same time, the positive electrode material in the embodiment of the present application can reduce the Rs and Rct of the battery, showing good rate performance, and the comprehensive electrochemical performance of the embodiment materials is better than that of the comparative example materials.
[0107] Comparing the data between Example 2 and Example 18, it is not difficult to see that when the material of the inner core is a single crystal (Example 2), the cycle performance of the material can be further improved, and it is also more conducive to improving the rate performance of the battery. Comparing the results of Example 2 and Examples 12-15, it can be found that when the content of the doping element is within the range further suggested in the embodiments of the present application, the overall performance of the final battery is better. Comparing the data between Example 2 and Example 17, it can be seen that when the shell layer of the positive electrode material has a doping element (Example 2), it is more conducive to improving the electronic / ionic conductivity of the positive electrode material, and the structural stability of the positive electrode material during the charge and discharge process can be further improved, thereby significantly improving the cycle performance of the battery.
[0108] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A positive electrode material, characterized in that: It includes a core and a shell layer coated on the core; wherein, the core includes (Li a A d ) 1+x (M 1-b E b ) 1-x (O 1-c L 2c )2, 0 < x ≤ 0.33, 0 < a ≤ 1, 0 ≤ b < 1, 0 ≤ c < 1, 0 ≤ d < 1; M includes at least one of Ni, Co, and Mn; A includes at least one of Na, K, and Mg; E includes at least one of Al, Mg, Cr, Co, Ce, Zr, Mo, Nb, W, Ta, B, Y, Sr, V, and Ti; L includes at least one of F, Cl, and Br; The shell layer includes WO 2.72 , and the WO 2.72 The mass proportion in the shell layer is ≥90%.
2. The positive electrode material according to claim 1, characterized in that The shell layer further includes a doping element, and the doping element includes at least one of Ni, Co and Mn.
3. The positive electrode material according to claim 2, characterized in that The mass percentage of the doping element in the shell layer is 0.05%-10%.
4. The positive electrode material according to any one of claims 1 to 3, characterized in that The thickness of the shell layer is in the range of 5nm-200nm.
5. The positive electrode material according to any one of claims 1 to 4, characterized in that Based on the mass of the positive electrode material, the mass proportion of the tungsten element in the shell layer is in the range of 0.05%-5%.
6. The positive electrode material according to any one of claims 1 to 5, characterized in that The kernel includes the (Li a A d ) 1+x (M 1-b E b ) 1-x (O 1-c L 2c )2 single crystal particles.
7. A method for preparing a positive electrode material, characterized in that: include: According to the (Li a A d ) 1+x (M 1-b E b ) 1-x (O 1-c L 2c )2, and performing a first calcination in an air atmosphere to obtain a first material; wherein M includes at least one of Ni, Co and Mn; A includes at least one of Na, K and Mg; E includes at least one of Al, Mg, Cr, Co, Ce, Zr, Mo, Nb, W, Ta, B, Y, Sr, V and Ti; and L includes at least one of F, Cl and Br; The first material, tungsten source, oxalic acid and solvent are mixed to obtain a mixture; the mixture is heated to react, and the obtained solidified material is subjected to a second calcination under a protective atmosphere to obtain a positive electrode material; the positive electrode material comprises a core and a shell layer coated on the core; wherein the core comprises (Li a A d ) 1+x (M 1-b E b ) 1-x (O 1-c L 2c )2, where 0 <x≤0.33,0<a≤1,0≤b<1,0≤c<1,0≤d<1; The material of the shell layer includes WO 2.72 , and WO 2.72 The mass percentage in the shell layer is ≥ 90%.
8. The method for preparing the positive electrode material according to claim 7, characterized in that: The method further comprises adding a compound containing a doping element into the mixture, wherein the doping element comprises at least one of Ni, Co and Mn.
9. A positive electrode, characterized in that The positive electrode comprises the positive electrode material according to any one of claims 1 to 6, or a positive electrode material prepared by the method for preparing the positive electrode material according to any one of claims 7 to 8.
10. A secondary battery, characterized in that: The secondary battery includes the positive electrode as claimed in claim 9.
11. An electrical device, characterized in that: The electric device comprises the secondary battery as claimed in claim 10.
Citation Information
Cited By
Positive electrode material and preparation method therefor, positive electrode, secondary battery, and electric device
WO2025130248A1